2015
DOI: 10.1371/journal.pone.0130083
|View full text |Cite
|
Sign up to set email alerts
|

Murine Efficacy and Pharmacokinetic Evaluation of the Flaviviral NS5 Capping Enzyme 2-Thioxothiazolidin-4-One Inhibitor BG-323

Abstract: Arthropod-borne flavivirus infection continues to cause significant morbidity and mortality worldwide. Identification of drug targets and novel antiflaviviral compounds to treat these diseases has become a global health imperative. A previous screen of 235,456 commercially available small molecules identified the 2-thioxothiazolidin-4-one family of compounds as inhibitors of the flaviviral NS5 capping enzyme, a promising target for antiviral drug development. Rational drug design methodologies enabled identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…(), Bullard et al. (), Chernesky (,b), Chernesky & Whittaker‐Haines (), Ebel et al. (), Flint et al.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…(), Bullard et al. (), Chernesky (,b), Chernesky & Whittaker‐Haines (), Ebel et al. (), Flint et al.…”
Section: Resultsunclassified
“…Two studies using small molecule compounds; 6‐azauridine, 2‐C‐methylcytidine and interferon alpha 2a did not report the magnitude of POWV inhibition (Flint et al., ; Osolodkin et al., ). However, two other potential antiflaviviral agents, the NS5 capping enzyme inhibitor BG‐323 (Bullard et al., ) and adenosine analog NITD008 (Yin et al., ), significantly reduced POWV titres in vitro in their respective studies. An I. scapularis organ culture model was developed to study the effects of POWV localization and replication to ultimately enhance screening for potential vaccine candidates and proteins for therapeutic use (Grabowski et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…This was supported by an earlier SAXS analysis which showed that the full length NS5 from DENV-3 could assume multiple conformations in solution, from compact to more extended forms(254). In the crystal structure of DENV-3 NS5, a well-ordered linker region (residues[263][264][265][266][267][268][269][270][271][272] between the MTase and RdRp domains was fully resolved for the first time.The linker comprises a short 310-helix (residues 263-266) which probably acts as a swivel, making structural transition to confer conformational flexibility of NS5 to perform its enzymatic functions and for interaction with viral and host proteins. Given the sequence heterogenicity of the linker residues across flaviviruses (Figure3.6) despite a conservation in the length of the linker region, we probed the relevance of their unique amino acid composition in our linker swapping experiment using DENV-2 subgenomic replicon system.…”
mentioning
confidence: 65%
“…BG-323 was shown to decrease guanylation activity in vitro, present antiviral efficacy in DENV replicon assay and inhibit replication of WNV and YFV. Moreover, resistance of WNV to the compound was not detected after long-term culture experiment (267). However, it is probable that the antiviral effect detected may be attributed to the compound interfering with the MTase activity of the capping enzyme or intervening with aldose reductase since BG-323 has a structure that resembles the known FDA-approved drug, Epalrestat, that targets this cellular protein for improving the conditions of patients with diabetic neuropathy (268).…”
Section: Inhibitors Of Rna Cappingmentioning
confidence: 99%
See 1 more Smart Citation